S. Kissin's literary mystification and the poem of V. Khodasevich "To the poet": the story of one exposure - Petrs-Bartsumian, Ani (Bulletin of Yerevan University H: Russian Philology, 2023)
The article is devoted to the literary mystification of Samuil Kissin (Mouni) and the history of its exposure. S. Kissin tried to incarnate in another person - Alexander Alexandrovich Beklemishev and construct a different author's "I", different from his own. The result of this experiment was several poems and the story "In the Summer of 190*", written in the wake of the life drama experienced by Kissin. The experience of such an incarnation had a hard effect both on Kissin himself and on his entourage, and in 1908, under the name of Elizaveta Maksheeva, V. Khodasevich published the poem “To the Poet”, which was supposed to put an end to Kissin’s difficult love story and his protracted life-creating experiment. Next, the nature of Kissin's literary mystification is examined in the light of the phenomenon of duality, as well as the dual specificity of the borderline state of both the characters and the author (authors) of the story. On the basis of diary entries, memoirs, the history of exposing the literary hoax of Kissin is studied, and a comparison of poems by Khodasevich ("To the Poet"), Derzhavin ("Anacreon in the Assembly"), Baratynsky ("What are you, days for!") and Beklemishev (" Hungry herds of my fields!..”), allows us to reveal the connection between these works, and ultimately the purpose of Khodasevich's publication. The article emphasizes the revealing function of Khodasevich's poem, and in the conclusion, the carnival essence of both the story "In the Summer of 190*" and the work of Khodasevich, who played a key role in the story of exposing Kissin's literary hoax, is affirmed.
Keywords: literary mystification; S. Kissin (Muni); Alexandr Beklemishev; Khodasevich; Derzhavin; duality